2008
DOI: 10.1007/s10653-008-9181-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil pollution in day-care centers and playgrounds in Norway: national action plan for mapping and remediation

Abstract: Systematic geochemical mapping based on sampling and analysis of surface soils (0-2 cm) has been carried out in several Norwegian cities. The soils in the oldest parts of the cities are contaminated with metals (especially Pb) and polycyclic aromatic hydrocarbons (PAH). Due to the fact that children are often in contact with surface soil, it was realized that special focus had to be directed towards soils in day-care centers and playgrounds. The first mapping and remedy program was initiated in Trondheim in 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 18 publications
1
37
0
1
Order By: Relevance
“…In areas where playgrounds, public gardens and parks are exposed to significant pollution levels, soil and dust from the ground may have toxic effects as a consequence of inhalation or ingestion by humans, particularly children, which poses major health hazards (Ljung et al 2007;Ottesen 2008;Reis et al 2013a). Soil ingestion is referred to in a number of case studies as a probable source of Pb exposure in children with elevated blood Pb levels in some areas.…”
Section: Introductionmentioning
confidence: 99%
“…In areas where playgrounds, public gardens and parks are exposed to significant pollution levels, soil and dust from the ground may have toxic effects as a consequence of inhalation or ingestion by humans, particularly children, which poses major health hazards (Ljung et al 2007;Ottesen 2008;Reis et al 2013a). Soil ingestion is referred to in a number of case studies as a probable source of Pb exposure in children with elevated blood Pb levels in some areas.…”
Section: Introductionmentioning
confidence: 99%
“…Field methods included collection of soil samples according to the Geo-Experimental Expertise Group (URGE -Euro Geo Survays) [5]. It is sampled by a network which is dictated by geomorphological structure of the terrain.…”
Section: Research and Test Methodsmentioning
confidence: 99%
“…) In Europe and the USA, CCA-treated wood has been specifically used in outdoor play equipment at child-care centres, school yards and public playgrounds, each (in Norway) having on average 1.5-2 m 3 CCA-treated wood. Studies in Norway and New Orleans have shown that low-to medium-grade As pollution (8-250 mg/kg) is common in the soils of children's playgrounds (Jartun et al, 2003;Mielke et al, 2010;Ottesen et al, 2008), and a maximum concentration in child-care centre soil of 1800 mg/kg has been recorded (Jartun et al, 2003). (Mielke, 1993;Ottesen et al, 1995;Haugland et al, 2008) Results of the content of Cr, Cu and As in 70 samples of CCA-treated wood from child-care centres in Trondheim, Norway, clearly demonstrate the importance of CCA-treated wood as a possible source for these elements (Table 10.4).…”
Section: Arsenic (As)mentioning
confidence: 99%